A step in the right direction: an open-design pedometer algorithm for dogs - Ladha, C.; Belshaw, Z.; O’Sullivan, J.; Asher, L. (BioMed Central, 2018)
Accelerometer-based technologies could be useful in providing objective measures of canine ambulation, but most are either not tailored to the idiosyncrasies of canine gait, or, use un-validated or closed source approaches. The aim of this paper was to validate algorithms which could be applied to accelerometer data for i) counting the number of steps and ii) distance travelled by a dog.